Alternative and aberrant splicing of human endogenous retroviruses in cancer. What about head and neck? —A mini review - Agoni, Lorenzo (Frontiers in Oncology, 2022)
Human endogenous retroviruses (HERVs) are transcribed in many cancer types, including head and neck cancer. Due to accumulating mutations at proviral loci over evolutionary time, HERVs are functionally defective and cannot complete their viral life cycle. Despite that, HERVs transcripts, including full-length viral RNAs and viral RNAs spliced as expected at the conventional viral splice sites, can be detected in particular conditions, such as cancer. Interestingly, non-viral related transcription, including aberrant, non-conventionally spliced RNAs have been reported as well. The role of HERVs transcription in cancer and its contribution to oncogenesis or progression are still debated. Nonetheless, HERVs may constitute a suitable cancer biomarker or a target for therapy. Thus, ongoing research aim both to clarify the basic mechanisms underlying HERVs transcription in cancer as well as exploit its potential toward clinical application. In this mini-review we summarize the current knowledge, the most recent findings, and the future perspectives of research on HERVs transcription and splicing, with particular focus on head and neck cancer.